All Eyes On Antarctica: ATCM XLIV - Hanne Nielsen; Bruno Arpi; Jeffrey McGee; Marcus Haward (2022)
The Forty-Fourth Antarctic Treaty Consultative Meeting is taking place in Berlin as a hybrid meeting. For the Antarctic Treaty Consultative Parties (ATCPs), it provides an opportunity to reassert their commitment to scientific research, international collaboration, and peace in Antarctica.